ANALYSIS OF SOCIAL AND ENVIRONMENTALLY CONSCIOUS BEHAVIOR AS PART IN COMPANIES - Vida, Viktória; Talatu, Maryam Alhassan (Applied Studies in Agribusiness and Commerce, 2025)
This research estimates public perceptions of corporate environmental responsibility and the use of clean energy in terms of how businesses exhibit environmentally sensitive behaviour through their operations and how clean energy is used within daily business operations. It carries out a large-scale survey among 100 participants, analyzing responses across various dimensions of corporate social responsibility, especially those relevant to environmental practices. The findings show that there is a high public expectation of business environmental responsibility, as 82% of the respondents regard it as very important for companies to undertake social responsibility activities. The same percentage (80%) feel it is essential that companies be liable for environmental damage. The same study also firmly focused on carbon emission reduction since 91% rated it somewhat or very important for companies to reduce their carbon emissions.On the other hand, a perception gap was indicated since 52% of the respondents strongly believed that companies genuinely care about their social and environmental impact. This contrasts with the 77% of participants publicly declaring support for corporations promising to reduce environmental degradation. On the use of clean energy, while the research does not give an explicit quantitative status of the practice by corporate entities, it generally creates a good case demonstrating popular support for such corporate initiatives. A 72% rated a firm's effort to reduce its carbon footprint as essential, representing a clear expectation of adopting clean energy within corporate operations. The study finds considerable public mandate for companies to engage in environmentally sensitive business practices, including using clean energy. It also calls for improving business environmental responsibility programs, better communication transparency, prioritizing clean energy, and using environmental initiatives to gain market advantage. The findings and recommendations carry significant implications for corporate strategy, public policy, and future research in corporate social responsibility and environmental sustainability.